Facilitating the coping and development of college students with mental disorders: a positive clinical psychology approach - Hu, Bo; Huang, Yuxin; Yao, Xinlei; Chen, Chaoyang (Frontiers in Psychology, 2024)
In serving college students with mental disorders, on-campus mental health professionals have been lacking integrative theoretical frameworks to guide their missions of prevention, remedy, and development facilitation. In the current paper, we propose the positive clinical psychology as a theoretically and practically valuable framework for these missions by narratively reviewing the preventive, remedial, and developmental mechanisms derived from the theory and summarizing the most recent empirical evidence that supports each mechanism. We further discuss why and how these mechanisms and findings can be applied to on-campus mental health services to facilitate the resilience and optimal development of college students with mental disorders. Particularly, the use of resilience-focused and strength-based intervention strategies are promoted for services.